Psychological Diagnostics During Pregnancy And In The Postpartum Period: Methods Review - Zhdanova, Iryna; Malieieva, Chrystyna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The article is devoted to a scientific analysis 9 of psychological problem diagnostics during pregnancy and in the postpartum period. It is proved that the current state of the mentioned problem in Ukrainian psychological science and practice is in crisis due to the absence or small number of psychodiagnostic methods adapted to the Ukrainian-speaking environment. Modern trends related to the orientation towards Western psychodiagnostics are still quite illusory, and the use of Russian-language methods has become impossible. This situation is observed in all areas of psychological practice, including perinatal psychology. The article provides an analytical review of scientific sources, which present the results and describe the methods of empirical research on the psychological aspects of pregnancy, such as: a woman’s attitude towards pregnancy, manifested by various types of the psychological component of gestational dominance; mother’s and father’s attachment to the unborn child; motives for maintaining pregnancy; perinatal and postpartum anxiety; postpartum depression. The main methods of psychological diagnostics that are most often used for research are analyzed (I.V. Dobryakov’s pregnant attitude test, MFA, PAI and MAAS methods for determining attachment to the child, L. Rabovalyuk’s method for studying the motives for maintaining pregnancy, the Perinatal Anxiety Screening Scale and Pregnancy-Related Anxiety Questionnaire – Revised-2, the Edinburgh Postpartum Depression Scale, the Correa-Barrick Postpartum Depression Scale). One of the models of the psychodiagnostic component of the program of psychological support for pregnant women, developed by Ukrainian scientists, is presented, which is aimed at assessing the psychoemotional sphere of a pregnant woman, the characteristics of her personality, self-esteem, value orientations, and the woman’s attitude to the situation of pregnancy, the unborn child, and motherhood in general. The differentiated approach to psychological diagnostics is emphasized, depending on the method of fertilization and the course of pregnancy. An approach to creating a psychodiagnostic complex for its use in psychological support of pregnant women, based on modern regulatory documents of the Ministry of Health of Ukraine, is proposed.